PERAN GURU PAI DALAM MEMBINA AKHLAKUL KARIMAH SISWA UNTUK MENCEGAH PERILAKU CYBERBULLYING DI MTS MUHZIRAH GALESONG SELATAN KABUPATEN TAKALAR - Muh. Awal; Nurul Aulia Warahmah; Nur Ain Syafikah; Rahmat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to describe the role of Islamic Religious Education (PAI) teachers in fostering good character (akhlakul karimah) among students as an effort to prevent cyberbullying behavior at MTs Muhzirah, Galesong Selatan, Takalar Regency. This research employed a qualitative descriptive method with a case study approach. Data were collected through observation, in-depth interviews with the PAI teacher, the headmaster, homeroom teachers, and students, and documentation studies, then analyzed using the Miles and Huberman model consisting of data reduction, data display, and conclusion drawing, and validated through source and technique triangulation. The results indicate that PAI teachers carry out their role through exemplary conduct, habituation of Islamic values, moral guidance and counseling, and the integration of digital-ethics material into classroom learning. Preventive efforts include instilling the values of honesty, empathy, and mutual respect, and socializing the dangers of cyberbullying through religious activities such as Jumat curhat and kultum. Supporting factors include cooperation with parents and school policy on gadget use, while inhibiting factors include limited supervision of students' social media activity outside school hours and the rapid development of digital platforms. The study concludes that the moral guidance carried out by PAI teachers contributes significantly to shaping students' character and reducing the tendency toward cyberbullying.